Bioconversion of pineapple wastes for production of Pleurotus pulmonarius (gray oyster mushroom) and Pleurotus ostreatus (white oyster mushroom) - Norliana, Munir; Aizi Nor Mazila, Ramli; Aimi Wahidah, Aminan; Sharifah Zafierah, Syed Badrulzaman; Vasant Patil, Reshma; Siti Zulaiha, Zailani; Nur Izyan, Wan Azelee; Nor Hasmaliana, Abdul Manas; Elmie Adha, Ismail (John Wiley and Sons Inc., 2024)
Mushroom cultivation is currently being widely ventured by farmers in Malaysia due to its high profits in a short time and low production cost. Mushrooms can be grown on various substrates such as rice husk and stalks, coconut fiber, and sawdust. This study was performed to find out the ability of using pineapple leaves waste as a substrate for the cultivation of Pleurotus pulmonarius (gray oyster mushroom) and Pleurotus ostreatus (white oyster mushroom) and compare the results obtained with mushrooms grown using traditional substrates (sawdust). The mushroom bags were prepared using a dry and wet medium of pineapple leaves waste. The results revealed that 60% of dry and wet pineapple leaves waste produced the highest output of P. pulmonarius and P. ostreatus in comparison to other percentages. The growing of P. pulmonarius on dry pineapple leaves waste substrate revealed the maximum average weight and number of fruiting bodies while P. ostreatus showed the best growth performance in wet pineapple leaves waste substrate. The nutritional content of 60% dry and wet pineapple leaves waste for both P. pulmonarius and P. ostreatus shown superior value in percentages of moisture, protein, fat, and carbohydrate compared to control. In the meantime, the mineral analysis revealed that 60% of the dry and wet pineapple leaves waste had greater levels of Cu, P, and Pb than the control. These findings suggested that the pineapple leaves waste can become a great alternative substrate for both P. pulmonarius and P. ostreatus cultivation for better economic and environmental benefits.